Further notes on the text and interpretation of Catullus - Heyworth, S; Trimble, G (Editrice Stilgraf, 2019)
The paper offers discussion of, and (in eight cases) new conjectures on, nine passages of Catullus: 11.9-12, 64.43-6, 64.105-11, 64.251-7, 65.15-24, 71, 97.1-5, 98, 99.5-6.